Serologic investigation of undifferentiated nasopharyngeal carcinoma and simian virus 40 infection. Issue 2 (16th June 2015) - Mazzoni, Elisa; Martini, Fernanda; Corallini, Alfredo; Taronna, Angelo; Barbanti–Brodano, Giuseppe; Querzoli, Patrizia; Magri, Eros; Rotondo, John Charles; Dolcetti, Riccardo; Vaccher, Emanuela; Tognon, Mauro
ABSTRACT: Background: The association between undifferentiated nasopharyngeal carcinoma (NPC) and Epstein–Barr virus (EBV) is well established. Nevertheless, available evidence suggests that other cofactors are required for the development of undifferentiated NPC. Several investigations reported simian virus 40 (SV40) footprints in human tumors of different histotypes. Methods: Serum samples from patients with undifferentiated NPC ( n = 64) and healthy subjects ( n = 130) were analyzed by an indirect enzyme‐linked immunosorbent assay (ELISA) with SV40 synthetic peptides to detect antibodies against viral peptide (VP) capsid proteins VP1, 2, and 3. Results: Immunologic data indicate that in sera from patients with undifferentiated NPC, the prevalence of SV40 antibodies was 25%, whereas in controls it was 16%. This difference is not statistically significant ( p > .05). Conclusion: A similar prevalence of SV40 antibodies was detected in undifferentiated NPC and healthy subjects. Our serologic data suggest no association between undifferentiated NPC and SV40 infection. This investigation may stimulate further studies aimed at determining the possible contribution of other risk factors in the pathogenesis of undifferentiated NPC. © 2015 Wiley Periodicals, Inc. Head Neck 38: 232–236, 2016